A bispecific decoy receptor VEGFR-EGFR/Fc binding EGF-like ligands and VEGF shows potent antitumor efficacy. (16th March 2022) - Guo, Xiao-Fang; Zhang, Yue-Yue; Kang, Jia; Dou, Qiao-Hua; Zhu, Xiao-Fei
Abstract: Epidermal growth factor receptor (EGFR) and vascular endothelial growth factor receptor (VEGFR) represent two clinically validated targets for a variety of human cancers, and dual inhibition of EGFR and VEGF(R) has demonstrated superior activity to single EGFR inhibitors. This study was to construct a novel bispecific decoy receptor VEGFR-EGFR/Fc that contains Fc portion of human IgG1 acted as molecular scaffold, and the immunoglobulin-like domain 1–3 of VEGFR1 and extracellular domain of EGFR fused to the N-terminal and C-terminal of Fc, respectively, aiming at capturing the EGF-like ligands and VEGF. ELISA showed that VEGFR-EGFR/Fc bound to EGF, TGF-α and VEGF with high affinity. It displayed potent proliferation inhibitory effects on human non-small-cell lung cancer A549 cells and human umbilical vein endothelial cells revealed by MTT assays. VEGFR-EGFR/Fc significantly inhibited cell invasion and migration demonstrated by wound healing assay and transwell assay. In vivo, VEGFR-EGFR/Fc showed remarkable growth inhibition on A549 xenografts. Cell apoptosis and inhibition of angiogenesis were also observed in xenograft tumour tissues. Mechanistically, VEGFR-EGFR/Fc pre-treatment blocked the phosphorylation of EGFR and VEGFR2 and resulted in a decrease in the downstream signalling molecules, AKT, p44/42MAPK and p38MAPK. These data suggest VEGFR-EGFR/Fc would be a promising candidate for cancer targeted therapy.